Đôi nét về đặc điểm tiêu đề bài học trong giáo trình khẩu ngữ tiếng Hán /Phạm Ngọc Hàm, Ngô Minh Nguyệt. - Phạm, Ngọc Hàm.
Title owns the most general value of content of lesson, the absorbability of the lesson partly depends on the attraction of the title. Through the title analysis of Chinese conversation lesson plans for sophomores of Faculty of Chinees Linguistics and Culture, University of Language and International Studies, Hanoi National University, the articles brings forward some features and roles of title of Chinees lesson.